Learning from The Leadership of Boaz in The Book of Ruth - Sia Kok Sin (Jurnal Jaffray, 2021)
This article addresses the study of the leadership of Boaz in the book of Ruth by using the leadership concept of Peter G. Northouse. Based on Northouse's concept, Boaz is an ideal and effective leader who can perform both as assigned and emergent leaders. The keys to the success of Boaz's leadership are his character and skills. First, this article will define the leadership concept of Peter G. Northouse. Northouse identifies the nature of leadership as an assigned leadership and emergent leadership. He also explains the powers that associate with the types of leadership. The appointed leadership has position power which consists of legitimate, reward, information, and coercive power. Emergent leadership has personal power that includes referent and expert power. Second, this article will examine the character of Boaz in the book of Ruth through the lens of the nature of leadership as an assigned leadership and emergent leadership. An observation of how Boaz performs the many types of power as an appointed leader and an emergent leader. Finally, this article will conclude how the leadership of Boaz is. Boaz is an ideal and effective leader who can perform both as an assigned and emergent leader. The keys to the success of Boaz's leadership are his character and skills.